Endoscopic endonasal transsphenoidal approach for sellar tumors beyond the sellar turcica. (March 2014) - Song, Yexun; Li, Heqing; Liu, Huowang; Li, Wei; Zhang, Xiaowei; Guo, Lian; Tan, Guolin
Abstract Conclusions: The endoscopic endonasal transsphenoidal approach can be a choice for sellar tumors beyond the sellar turcica, but it is necessary to make the choice carefully because of the severe surgical risks. Objectives: To summarize our experience of removal of sellar tumors beyond the sellar turcica via the endoscopic endonasal transsphenoidal approach and to evaluate the surgical efficacy and complications. Methods: Between January 2007 and January 2012, 30 patients with sellar tumors beyond the sellar turcica underwent surgery using the endoscopic endonasal transsphenoidal approach. Results: Postoperative pathological examination demonstrated that pituitary adenoma occurred in 22 patients, craniopharyngioma in 5, and meningioma in 3. Total removal was achieved in 21 patients (70.0%) and subtotal removal was achieved in 8 patients (26.7%). After the surgery, cerebrospinal fluid leakage occurred in 3 patients, temporary diabetes insipidus occurred in 25 patients and persistent diabetes insipidus in 4 patients, intracranial infection occurred in 1 patient, frontal subdural effusion occurred in 1 patient, sinusitis occurred in 2 patients, epistaxis occurred in 3 patients, and 1 patient with a huge pituitary adenoma died of hypothalamic failure related to the operation.